Air pollution in urban areas and health effects - Haliza Abdul Rahman, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
The world’s population is becoming ever more urbanised, causing deterioration of air quality in many of the most rapidly growing cities. The common air pollutants include carbon monoxide, nitrogen dioxide, ozone, particulate matter, sulphur dioxide and lead. In their most extreme form, air pollution episodes are accompanied by physical discomfort, disruption of day-to-day living, widespread public fear, illness and even death.In many cities air pollution is reaching levels that threaten people’s health according to an unprecedented compilation of air quality data released today by WHO. For example, a study of air pollution in 20 of the 24 megacities of the world shows that ambient air pollution concentrations are at levels where serious health effects are reported. Moreover, in year 2004, urban air pollution is ranked as the 14th global risk factor for mortality. For 2008, the estimated mortality attributable to outdoor air pollution in cities amounts to 1.34 million premature deaths. Thus, epidemiological studies have consistently associated adverse health effects with exposures to particulate air pollution. However, the effects of air pollution on health are dependent on several factors. Apart from the concentrations and chemical properties of the pollutants, the person’s age and general state of health, the duration of exposure, factors such as the weather condition and the distance from the emission sources also affect the nature and extent of the health effects observed.Therefore, the ambient air quality is much urgency in instituting control and preventive measures and at the public level there is a long-standing commitment to improve air quality.